Knowledge Management in the 21st Century: Trends, Developments, and Strategies - Tong Wooi, CHOW (Jerry) (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In the evolving landscape of the 21 st-century, the sphere of knowledge management (KM) has greatly transformed over the years, boosted by means of technological advancement as well as changes in organizational structures. Research has shown that knowledge management is becoming increasingly important for organizations to achieve their goals and stay competitive in today's changing environment. This article focuses on the changes that have an impact on the knowledge management of organizations. The research approach employs the review of published knowledge management literature postulating on these related changes and development. The write-up included the overview of four firms as case studies, namely, Xerox Corporation, Siemens AG, Carnegie Mellon University’s School of Computer Science (SCS) and Imperial College London’s Data Science Institute (DSI). There are key lessons worth reflecting on from these organizations’ implementation of knowledge management. As the knowledge management landscape continues to evolve, the paper serves as a valued reference for all those who are taking part in industries, scholars and students and agencies who wish to harness knowledge excellence and innovation. It proposes an integrated model of knowledge-sharing culture, technology, and strategies for best practice and a framework for the strategies of knowledge management is included. Review findings affirm that organizations need to adopt effective and efficient knowledge management practices for organizations to stay competitive and improve performance. The paper concludes with the recommendation that knowledge management is required for organizational efficiency in the digital era and outlines insights on strategies for best practices.